Synthesis of sulfonyloxy furoxans via hydroxyfuroxan ammonium salts. Issue 27 (5th July 2018) - Matsubara, Ryosuke; Katsuragi, Yuki; Sakaguchi, Takaya; Eguchi, Shuhei; Hayashi, Masahiko; Ando, Akihiro
Abstract: Furoxans are distinctive heteroaromatic compounds in that they are potentially capable of releasing nitric oxide under physiological conditions. In order to utilize the furoxan scaffold for the development of functional molecules, synthetically relevant functional groups are required for access to diverse furoxans. In this report, a facile route to furoxans with sulfonyloxy groups, which are halide surrogates, has been developed. The key features of this strategy include the synthesis and utilization of bench-stable hydroxyfuroxan salts, the use of sulfonyl anhydrides in the sulfonylation step instead of sulfonyl chlorides, and the photochemical isomerization of one regioisomer to another in order to gain access to both. Graphical abstract: Image 1